2003
DOI: 10.1128/jb.185.15.4442-4449.2003
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Biochemical Characterization of the F 1 F o -ATP Synthase from Thermoalkaliphilic Bacillus sp. Strain TA2.A1

Abstract: We describe here purification and biochemical characterization of the F 1 F o -ATP synthase from the thermoalkaliphilic organism Bacillus sp. strain TA2.A1. The purified enzyme produced the typical subunit pattern of an F 1 F o -ATP synthase on a sodium dodecyl sulfate-polyacrylamide gel, with F 1 subunits ␣, ␤, ␥, ␦, and and F o subunits a, b, and c. The subunits were identified by N-terminal protein sequencing and mass spectroscopy. A notable feature of the ATP synthase from strain TA2.A1 was its specific bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
71
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(78 citation statements)
references
References 48 publications
(72 reference statements)
7
71
0
Order By: Relevance
“…To confirm that DCCD predominantly reacted with the c subunit in our experiments, we tested whether the bulk ATPase activities of F 0 F 1 recovered from the DCCD inhibition by adding the detergent LDAO. LDAO is known to decouple the ATPase activity of F 1 from the H ϩ -conducting activity of F 0 and thus restore the F 0 F 1 ATPase activity in the presence of LDAO (32). As expected, when 0.2% (w/v) LDAO was added after a 10-min incubation of 1 mM DCCD, more than 80% of the ATPase activity was recovered (Fig.…”
Section: ϫ5mentioning
confidence: 56%
See 1 more Smart Citation
“…To confirm that DCCD predominantly reacted with the c subunit in our experiments, we tested whether the bulk ATPase activities of F 0 F 1 recovered from the DCCD inhibition by adding the detergent LDAO. LDAO is known to decouple the ATPase activity of F 1 from the H ϩ -conducting activity of F 0 and thus restore the F 0 F 1 ATPase activity in the presence of LDAO (32). As expected, when 0.2% (w/v) LDAO was added after a 10-min incubation of 1 mM DCCD, more than 80% of the ATPase activity was recovered (Fig.…”
Section: ϫ5mentioning
confidence: 56%
“…After the ATP hydrolysis activity reached steady state, 0.2% (w/v) lauryldimethylamine oxide (LDAO) was added to confirm the reactivation of the activity. It has been reported that LDAO activates DCCD-inhibited F 0 F 1 by inducing the uncoupling of F 0 and F 1 (32).…”
Section: Methodsmentioning
confidence: 99%
“…Proton permeability was determined in membrane vesicles by monitoring the change in external pH with the fluorescent pH probe pyranine (pK a 7?3, excitation and emission wavelengths of 450 and 508 nm respectively), as described by van de Vossenberg et al (1995). The preparation of membrane vesicles of M. smegmatis and B. subtilis was based on previously described protocols (Cook et al, 2003;Rao et al, 2001). These vesicles were prepared with a high buffering capacity on the inside (50 mM MOPS, pH 7?0, 75 mM KCl and 25 mM choline chloride), and dispersed into a solution (2 mg protein ml 21 ) of low buffering capacity (0?5 mM MOPS, pH 7?0, 75 mM KCl and 75 mM sucrose), containing 10 mM pyranine.…”
Section: Methodsmentioning
confidence: 99%
“…Organism-specific environmental factors, such as temperature or pH, also do not provide a consistent rationale; for example, ATP synthases from thermoalkaliphilic bacteria use a H + gradient despite the scarcity of H + and the potentially greater degree of H + leakage across the membrane at high temperatures, compared with Na + (12,13). Indeed, pmf-and smf-driven systems are often found within the same organism, and sometimes with the same or similar function; for example, malate uptake in Bacillus subtilis is mediated by the H + -coupled symporter CimH (14) and by the Na + -coupled MaeN (15).…”
mentioning
confidence: 99%